2023
DOI: 10.1039/d2nj05462k
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the catecholase activities and DNA binding interaction of mono-, di-, and polymeric Cu(ii) complexes derived from heterogeneous Schiff base ligands

Abstract: A mononuclear, dinuclear, and a polymeric Cu(II) complexes of the general formula [Cu(L1)Cl2] (1), [Cu2(L2)2(µ1.1-CH3COO-)2] (2), and [Cu2(L3)2(µ-N3)(N3)]n (3) have been synthesized using NNN and NNO tridentate Schiff base ligands...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…42,43 Several dicopper(II) complexes have been reported that can function as useful model systems for catecholaselike activity, [34][35][36][37][38][39][40][41]43 but only a few mononuclear copper(II) complexes have been reported with such an activity. [44][45][46][47][48][49][50][51] Copper(II) Schiff base coordination complexes with sophisticated designs are also useful for the study of protein-complex interaction, which is another encouraging area to explore. 44,55,57,[105][106][107][108] In many biochemical processes, protein-complex interaction studies have revealed the role of albumins in both healthy and diseased states.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Several dicopper(II) complexes have been reported that can function as useful model systems for catecholaselike activity, [34][35][36][37][38][39][40][41]43 but only a few mononuclear copper(II) complexes have been reported with such an activity. [44][45][46][47][48][49][50][51] Copper(II) Schiff base coordination complexes with sophisticated designs are also useful for the study of protein-complex interaction, which is another encouraging area to explore. 44,55,57,[105][106][107][108] In many biochemical processes, protein-complex interaction studies have revealed the role of albumins in both healthy and diseased states.…”
Section: Introductionmentioning
confidence: 99%
“…To get significant insights about the chemotherapeutic activities of any bioactive molecule, the binding affinity investigation of that molecule with DNA and BSA/HSA is very important, as for almost all the anticancer and antifungal drugs, DNA is the target macromolecule, and serum albumins are the most soluble plasma proteins that have the capability to transport those drugs. , There are mainly three types of interactions that occur with DNA (intercalation, groove binding, and surface interaction) which are altered due to the change in the metal ion or the ligands of metal complexes. Therefore, in the design of effective metal complexes as drugs, binding affinity investigation of these complexes with DNA and BSA/HSA is very crucial. Hence, before progressing to model experiments, we assessed the potential of our synthesized compound by testing it on commercially available DNA and BSA.…”
Section: Introductionmentioning
confidence: 99%